Vechornytsi (Life is a cabaret) - Gordey, Gordon; Ganert, Dave (My University, 2013)
Video performance excerpts of Vechornytsi-Life is a Cabaret edited in 2013 featuring live performances with orchestra and on stage projected video. Six cabaret style contemporary original dance works are featured to upbeat re-envisioned folk songs in a pop style including the classical style Melodia by Ukraine composer, Mykola Skoryk. These danceworks were created for The Ukrainian Shumka Dancers of Canada.
Keywords: Ukrainian Shumka Dancers; Ukrainian dance; folk dance; Canadian dance; contemporary Ukrainian dance; Brian Cherwick; Oleh Skrypka; Ukrainian pop music; Vasyia Club; Mykola Skoryk